Evaluation of meibomian glands in childhood malnutrition - Fuat Yavrum; Begüm Yavrum; Elmas Yüksel-Şükün; Nedime Sahinoglu-Keskek (Scientific Reports)
Abstract Childhood malnutrition is a condition that affects a large population and can have significant implications for eye health. Our study aims to assess the impact of childhood malnutrition to the ocular surface by evaluating meibomian gland morphology and function. This study included 92 patients aged 6–18 years, with 52 diagnosed with malnutrition and 40 serving as healthy controls. Patients’ nutritional status was determined based on body mass index (BMI) according to WHO criteria. Meibomian gland morphology and function were assessed using non-invasive imaging techniques and clinical evaluations along with the bloodwork results, including serum ferritin, hemoglobin, serum 25-hydroxyvitamin D, and vitamin B12 levels. Children with malnutrition exhibited significantly lower mean BMI, hemoglobin, serum 25-hydroxyvitamin D, serum ferritin levels and significantly worse meibomian gland loss (MGL) compared to healthy controls (p < 0.001 for all). However, differences in mean non-invasive tear break-up time (NI-BUT) and vitamin B12 levels were not statistically significant. Subgroup analysis based on malnutrition severity revealed no significant differences in MGL or NI-BUT levels. Negative correlations were observed between BMI and MGL, as well as between MGL and serum ferritin and 25-hydroxyvitamin D levels (p < 0.001 for all). This study provides novel insights into the ocular consequences of malnutrition in children, highlighting significant alterations in meibomian gland morphology and function associated with nutritional deficiencies. These findings may inform targeted interventions to reduce ocular morbidity and improve the overall health outcomes of malnourished children.